Epidemiological profile of exogenous poisoning in children and adolescents from a municipality in the state of Mato Grosso - Felipe Ferreira S. Oliveira; Eliane Aparecida Suchara (Sociedade de Pediatria de São Paulo, 2014)
OBJECTIVE: To study the epidemiology of exogenous intoxications in children and adolescents of Barra Garças, Mato Grosso, from January 2008 to September 2013.METHOD: This was a cross-sectional, retrospective, and descriptive epidemiological study. Data were collected from the Disease Notification System (Sistema de Informação de Agravos de Notificação [SINAN]) of the municipality, processed using Microsoft Excel, and evaluated through BIOESTAT statistical software. The variables included were: sex; age; toxic agent; time and place of service; route of administration; circumstance; and classification of intoxication. The age range was established according to the Brazilian Institute of Geography and Statistics, comprising children aged from 0 to 9 years old and adolescents aged from 10 to 19 years old.RESULTS: A total of 125 cases of accidental exogenous poisoning was registered, including 77 children and 48 adolescents. Food and beverages (38.4%) and drugs (24.0%) were the most common groups of toxic agents responsible for the poisoning. The largest age group affected by intoxication was composed of children aged from 0 to 4 years old (43.2%) and adolescents aged from 10 to 14 years old (19.7%). Regarding the circumstances, intoxication occurred due to suicide attempts (16.8%) and accidental events (23.2%) in adolescents and children, respectively. The study revealed a higher frequency of poisoning in girls.CONCLUSION: Exogenous intoxications occurred predominantly in children up to 4 years old, through the accidental consumption of food or drinks. Thus, the adoption of educational prevention programs for children's family members and caregivers is necessary.